Duration of Fixation in Patients with Acquired Brain Injury: Retrospective Analysis. - Lee, Kelly Sung H.; London, Richard (Optometry & Visual Performance, 2015)
Background: The use of objective eye movement measuring devices, such as the Visagraph or ReadAlyzer, has gained popularity in patients with acquired brain injury (ABI) in order to address their common complaints of reading difficulty. Based on our clinical experience, we have found a specific recording pattern in these patients, where the duration of fixation is increased proportionally greater than other test findings. Methods: A retrospective research study was conducted to determine the characteristics of Visagraph/ReadAlyzer results in 36 patients with ABI. Results: Our results show that out of 36 patients, 75% showed a pattern where the duration of fixation was increased, and a reduction of at least two grade levels as compared to the second-lowest component of the recording was present. Conclusion: It is common to see increased duration of fixation in patients with a history of ABI. This may indicate a reduction in information processing. Tachistoscopic activities, as a part of a vision rehabilitation program, will be beneficial for these patients in order to improve their reading ability further.